Role of Corporate Governance Moderating Effect of Risk Management on Company Performance: Evidence from Manufacturing Companies MM2100 Industrial Estate, Indonesia - Endah Prawesti Ningrum; Tri Yulaeli (Academic Bright Collaboration, 2026)
Purpose – In manufacturing firms situated in the MM2100 industrial region, this study intends to investigate the impact of risk management on business performance as well as the moderating function of corporate governance.Methods – Partial Least Squares Structural Equation Modeling (PLS-SEM) is the quantitative method used in this investigation. 153 respondents in managerial roles provided the data on manufacturer company on MM2100 Industrial Estate, Indonesia, guaranteeing its applicability to strategic decision-making procedures.Findings – The findings show that risk management improves company performance but is statistically insignificant. On the other hand, business performance is positively and significantly impacted by corporate governance. Stronger governance systems may lessen the impact of risk management methods on performance outcomes, since corporate governance is also proven to negatively and considerably modify the link between risk management and business performance.Research Implications – These results imply that corporate governance structures' ability to facilitate flexibility and strategic integration influences risk management's efficacy in addition to its execution. Overly strict governance may make managers less adaptable when implementing risk management plans, as reflected in the significant negative moderating effect (coefficient = -0.393) and the model’s explanatory power (Adjusted R² = 0.562).Originality – By treating corporate governance as a moderating variable rather than just an independent or mediating factor, this study is unique. It contributes to a more nuanced understanding of the relationship between governance structures and risk management procedures in improving business performance by showing how better governance might lessen the efficacy of risk management.